Model for quality assessment in small farms in Cape Verde - Saraiva, M.; Rosa, A.; Simões, E.; Pires, A. R. (Innovation in small-farm agriculture: Improving livelihoods and sustainability, 2022)
This study aims to perform a holistic quality assessment of Cape Verdean agricultural sector. To achieve this objective, we have constructed an innovative model – SQual4Agri – where the farming units’ internal dimension, external context, and the productivity itself were all brought up together. It includes instruments to assess Farmers' satisfaction toward the quality of services provided by the public departments, quality metrics to assess the organizational items in farming organization plus estimation of production. For the development of the (SQual4Agri) model, the researchers built a specific survey validated by experts in focus groups. After interpreting the collected data, the following phase was to adapt the instrument of the 5 Senses (5Ss) for small agricultural instances, and, finally, adapting the SERVPREF for the evaluation of rural services provided by official authorities. With the application of the SQual4Agri model in the Poilão Dam irrigation perimeter where seventy farmers were involved, we have concluded that it is quite needed and relevant the implementation of quality techniques and methodologies in agricultural production units. Another finding was, there is a lack of Cape Verde Farmers' awareness and information upon benefits with organizational development with special regard to quality issues. This evidence is positively related to findings in prior studies by Simões and Saraiva (2014) and Simões (2018), conducted in the islands of S. Nicolau and Santiago, respectively. The third finding indicates widespread dissatisfaction with the services provided by the Ministry of Agriculture and the Environment of Cape Verde. Despite this dissatisfaction, it is perceived that the farmer is satisfied with his own activity. This contradictory element may show the fatigue and discouragement caused by the difficulties of agriculture in Cape Verde and difficulties in the implementation of public policies in this area. The application of the SQual4Agri model also indicates large potential for public policies changing in the rural contexts with impacts on efficiency, quality, and productivity.